Excessive Indulgence Of Parents and Social Consensus for Children Kindergarten - سوزان عبد الله محمد (College of Education for Women, 2019)
Parental socialization trends impacting seriously on the growth of individual personality and psychological health trends ,love, acceptance and on confidence help children to grow as a person who loves other accept others and trust and negative parental attitudes such as excess portents us or negligence . and the focusing and demonstrate a negative impact on the growth of excess an mental health and family play a significant role in a childes life we can see how many manifestation of compatibility or incompatibility thatappear on individual behaviors and achieve their success or failure in life be returned to the of human relations that prevailed between the family members of children in various stages of his life first and to methods of treatment parents faced in his life .So the researcher has developed the following goals : 1- Measurement method of excess indulgence towards kindergarten. 2- Identify the differences in the level of style excess indulgence towards kindergarten according to a variable: A-gender (male - female) B-stage (pre - kindergarten) 3-Measure the social harmony in kindergarten . 4-Identify the differences in the social harmony depending on the variable : A-gender (male - female) B-stage (pre -kindergarten) 5- Identify the link between relationship style of pampered excess for parents and social harmony for kindergarten the research sample consisted of (400) children from children in Riyauh Baghdad \ Rusafah second the paragraphs were prepared to demonstrate scale overloud be (18) . the preparation of the scale of the unanimous harmony and paragraphs be of (22) and after using statistical methods , the following : 1- the first objective findings indicate that parents of well . Travelled pampering method overload with their children , and the overage grades of the scale ( 61.07) 2-Notes the outcome of the second objective : A-the absence of significant difference in the degree of use of excessive indulgence method parents towards their children depending on gender section . B-the results suggest on statistically significant use of excessive indulgence method parents towards their children depending on the type of stage the calculated value of T (0.47),is smaller than the T-value 3-the third objective result indicate that kindergartens are in compatible socially . 4-the results of the fourth objective : A-this result shows that male lesser female looking either. B-indicate that the kindergarten (pre - kindergarten) they match the degree of lock of social consensus . 5-the latter objective result indicate existence of correlation between then the more the style of pampered excess by parents toward children worsened.